2021
DOI: 10.3390/pharmaceutics13030423
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible DNA/5-Fluorouracil-Gemini Surfactant-Functionalized Gold Nanoparticles as Promising Vectors in Lung Cancer Therapy

Abstract: The design and preparation of novel nanocarriers to transport cancer drugs for chemotherapy purposes is an important line of research in the medical field. A new 5-fluorouracil (5-Fu) transporter was designed based on the use of two new biocompatible gold nanosystems: (i) a gold nanoparticle precursor, Au@16-Ph-16, stabilized with the positively charged gemini surfactant 16-Ph-16, and (ii) the compacted nanocomplexes formed by the precursor and DNA/5-Fu complexes, Au@16-Ph-16/DNA–5-Fu. The physicochemical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…Therefore, the results obtained with TEM studies on C I and N I samples showed that small size spherical nanoparticles usually enter and exit the cell more efficiently [ 16 , 90 ]. Thus, the high degree of internalization obtained for the nanosystems used was in line with previous research on the cellular uptake of different nanoparticles [ 38 ]. The effects of these nanosystems on the cells are reflected in the data presented on cell viability, where they are enhanced for the smaller C 1 and C 1 + N 1 ( Figure 14 ).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Therefore, the results obtained with TEM studies on C I and N I samples showed that small size spherical nanoparticles usually enter and exit the cell more efficiently [ 16 , 90 ]. Thus, the high degree of internalization obtained for the nanosystems used was in line with previous research on the cellular uptake of different nanoparticles [ 38 ]. The effects of these nanosystems on the cells are reflected in the data presented on cell viability, where they are enhanced for the smaller C 1 and C 1 + N 1 ( Figure 14 ).…”
Section: Resultssupporting
confidence: 87%
“…To study the internalization of the different treatments, a transmission ele microscopy study was carried out. For this study, cells were fixed after a 24 h treat to ensure that the nanosystems had entered the cells [38]. The study was carried ou Au@16-Ph-16 (N3), Au@16-Ph-16/DNA/Doxo (C3) and Au@16-Ph-16/DNA/Doxo + A To study the internalization of the different treatments, a transmission electron microscopy study was carried out.…”
Section: Internalization Of Au@16-ph-16 and Au@16-ph-16/dna-doxo Nano...mentioning
confidence: 99%
See 3 more Smart Citations